Comparative genome analysis reveals high-level drug resistance markers in a clinical isolate of Mycobacterium fortuitum subsp. fortuitum MF GZ001 - Alam, Md Shah; Guan, Ping; Zhu, Yuting; Zeng, Sanshan; Fang, Xiange; Wang, Shuai; Yusuf, Buhari; Zhang, Jingran; Tian, Xirong; Fang, Cuiting; Gao, Yamin; Khatun, Mst Sumaia; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Abstract Infections caused by non-tuberculosis mycobacteria are significantly worsening across the globe. In this study, we have identified and sequenced the genome of a clinical isolate of M. fortuitum subsp. fortuitum strain herein referred to as MF GZ001. Bacterial growth kinetics and morphology confirmed that MF GZ001 is a rapidly growing species with a rough morphotype. The MF GZ001 contains 6413573 bp genome size with 66.18 % high G+C content. MF GZ001 possesses a larger genome than other related mycobacteria and included 6156 protein-coding genes. Molecular phylogenetic tree, collinearity, and comparative genomic analysis suggested that MF GZ001 is a novel member of the M. fortuitum complex. We carried out the drug resistance profile analysis and found single nucleotide polymorphism (SNP) mutations in key drug resistance genes such as rpoB, katG, AAC(2')-Ib, gyrA, gyrB, embB, pncA, blaF, thyA, embC, embR, and iniA. In addition, the MF GZ001 strain contains mutations in iniA, iniC, pncA, and ribD which conferred resistance to isoniazid, ethambutol, pyrazinamide, and para-aminosalicylic acid respectively, which are not frequently observed in rapidly growing mycobacteria. A wide variety of predicted putative potential virulence genes were found in MF GZ001, most of which are shared with well-recognized mycobacterial species with high pathogenic profiles such as M. tuberculosis and M. abscessus. Therefore, the emergence of a novel member of the M. fortuitum complex will provide the foundation for further investigation of mycobacterial pathogenicity.